2013
DOI: 10.3758/s13423-013-0389-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subliminal hints on insight problem solving

Abstract: Two experiments tested a total of 509 participants on insight problems (the radiation problem and the nine-dot problem). Half of the participants were first exposed to a 1-min movie that included a subliminal hint. The hint raised the solution rate of people who did not recognize it. In addition, the way they solved the problem was affected by the hint. In Experiment 3, a novel technique was introduced to address some methodological concerns raised by Experiments 1 and 2. A total of 80 participants solved the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
28
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 31 publications
(29 reference statements)
4
28
1
1
Order By: Relevance
“…Analogical problem‐solving refers to solving the target problem by applying knowledge relating to solutions to other problems (i.e., bases) that have an analogous structure to that of the target issue. Contrary to Gick and Holyoak (), who suggested that a hint must be acknowledged as a hint to have its effect, Hattori et al () claimed that a subliminal hint can function as a primer. However, Hattori et al’s findings also differ from those of the aforementioned Jaušovec (), who did not observe hints having any influence on individuals in positive affective states.…”
Section: Methodsmentioning
confidence: 92%
See 4 more Smart Citations
“…Analogical problem‐solving refers to solving the target problem by applying knowledge relating to solutions to other problems (i.e., bases) that have an analogous structure to that of the target issue. Contrary to Gick and Holyoak (), who suggested that a hint must be acknowledged as a hint to have its effect, Hattori et al () claimed that a subliminal hint can function as a primer. However, Hattori et al’s findings also differ from those of the aforementioned Jaušovec (), who did not observe hints having any influence on individuals in positive affective states.…”
Section: Methodsmentioning
confidence: 92%
“…The hint stimulus in the hint condition was similar to that used by Hattori et al (, Experiment 1). The figural hint image was presented as part of a 60‐s movie, which was composed using one hint image (exposed 33 ms × 60 times), two mask images, three filler images, and one fixation image (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations